2013
DOI: 10.4048/jbc.2013.16.1.40
|View full text |Cite
|
Sign up to set email alerts
|

STAT3, a Poor Survival Predicator, Is Associated with Lymph Node Metastasis from Breast Cancer

Abstract: PurposeThe aim of this study is to explore signal transducer and activator of transcription 3 (STAT3) expression in breast cancer and to analyze the detailed mechanism that STAT3 contributes to the progression of breast cancer.MethodsWe retrospectively analyzed the clinicopathologic characteristics and overall survival (OS) of 140 breast cancer patients after curative surgery, and detected STAT3 expression, phosphorylated STAT3 (pSTAT3) expression, Ki-67 expression, vascular endothelial growth factor (VEGF)-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 26 publications
1
38
0
1
Order By: Relevance
“…Additionally, the transcription and translation of the STAT3 target gene SOCS3 was attenuated by CK2 inhibition, supporting the functional consequences of STAT3 inhibition. These results have clinical significance, as STAT3 activation has been associated with late-stage, metastatic breast cancer [45, 46]. Thus, CK2 inhibition may be able to functionally replace inhibitors of STAT3, which have had difficulty reaching the clinic [47].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the transcription and translation of the STAT3 target gene SOCS3 was attenuated by CK2 inhibition, supporting the functional consequences of STAT3 inhibition. These results have clinical significance, as STAT3 activation has been associated with late-stage, metastatic breast cancer [45, 46]. Thus, CK2 inhibition may be able to functionally replace inhibitors of STAT3, which have had difficulty reaching the clinic [47].…”
Section: Discussionmentioning
confidence: 99%
“…Recently silybin has shown to inhibit the phosphorylated signal transducer and activator of transcription protein-3 (pSTAT3; ref. 23), a marker of poor prognosis for many cancers, including breast (24). In a preclinical model of human gastric cancer, Wang and colleagues reported that the mechanism of action of silybin was related to a specific suppression of pSTAT3 and downregulation of STAT3 target genes, including Mcl-1, Bcl-xL, and survivin (25).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue samples were analyzed in one batch for SIL and in two batches for TOT-SIL determination. Each batch included standards (range, 2-500 ng/g) and controls (6,24, and 400 ng/g). We used a subrogate matrix of pig muscle (Clinobs) for the preparation of standards and controls.…”
Section: Analysis Of Silybinmentioning
confidence: 99%
“…Constitutive STAT3 activation is frequently found in nearly all human cancers, and expression levels of p-STAT3(Y705) are often associated with poor prognosis (13)(14)(15). Mechanisms driving STAT3 activation in cancer are incompletely understood.…”
Section: Discussionmentioning
confidence: 99%